2018
DOI: 10.15407/agrisp5.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of potato leafroll virus (PLRV) in mammalian continuous cell lines

Abstract: Aim.To use the ability of potato leafroll virus (PLRV) to infect and multiply in mammalian continuous cell lines to purify PLRV isolates from the vegetative plant material, and to study the pathogenicity of those isolates for plants (after culturing in mammalian continuous cell line), to investigate morphological, physical-chemical, biological and antigen properties of PLRV isolates from mammalian cells and to study an alternative diagnostic method -the neutralization test in the mammalian continuous cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Виділення та культивування вірусів проводили в перещеплюваних культурах клітин нирки ембріону свині (СНЕВ) та нирки новонародженого сірійського хом'яка (ВНК-21). Гіперімунні сироватки крові одержували на кролях за схемою розробленою нами [7].…”
unclassified
“…Виділення та культивування вірусів проводили в перещеплюваних культурах клітин нирки ембріону свині (СНЕВ) та нирки новонародженого сірійського хом'яка (ВНК-21). Гіперімунні сироватки крові одержували на кролях за схемою розробленою нами [7].…”
unclassified
“…As a result of studying the antigenic properties of the strain Dniprovsky-34 in RN with reference strains, it was found that the strain indicated antigenically related to PTV-1 Talfan, Teschen 199, Tirol, C 2372 at 100% and does not enter into serological responses with reference strains of other serotypes of PTV, PSV and EV-G. High antigenic affinity to the epizootic and reference strains of PTV-1 and high immunogenicity led to the selection of the strain Dniprovsky-34 as a production. According to the results of commission tests, the Dniprovsky-34 strain was deposited with the Depository of the State Scientific-Control Institute for Biotechnology and strains of microorganisms under the registration number 486 and the patent of Ukraine was obtained for a utility model [8].…”
mentioning
confidence: 99%